The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.3892/etm_00000089
|View full text |Cite
|
Sign up to set email alerts
|

Advanced malignant melanoma responds to Prunus mume Sieb. Et Zucc (Ume) extract: Case report and in vitro study

Abstract: Abstract. malignant melanoma (mm) is an aggressive chemoresistant skin cancer characterized by rapid metastasis and a poor prognosis. therefore, the development of innovative effective therapies is critical. mK615 is an extract from the Japanese apricot Prunus mume Sieb. Et Zucc (ume). at a neutral ph, it contains natural chemical substances such as triterpenoids that exert anti-neoplastic effects in several types of cancers. We found that in patients with advanced mm, mK615 dramatically suppressed the cutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…In addition, it is worthy of note that a range of concentrations (≤10 μg/ml) of Maesil extract employed in this study are likely to be physiologically and clinically rele- an extract of the Prunus mume, is able to relieve severe symptoms of patients with cancer when 6.5 g of MK615 was administered twice per day [12]. Based on this and other data, the effective concentrations (≤10 μg/ml) of Maesil extract used in this study are comparable to doses administrated in clinical and in vivo studies [12,23]. It is also noteworthy that an advantage of using whole extracts seems likely to appear unexpected efficacy caused by unknown compounds in the whole extracts.…”
Section: Resultssupporting
confidence: 52%
“…In addition, it is worthy of note that a range of concentrations (≤10 μg/ml) of Maesil extract employed in this study are likely to be physiologically and clinically rele- an extract of the Prunus mume, is able to relieve severe symptoms of patients with cancer when 6.5 g of MK615 was administered twice per day [12]. Based on this and other data, the effective concentrations (≤10 μg/ml) of Maesil extract used in this study are comparable to doses administrated in clinical and in vivo studies [12,23]. It is also noteworthy that an advantage of using whole extracts seems likely to appear unexpected efficacy caused by unknown compounds in the whole extracts.…”
Section: Resultssupporting
confidence: 52%
“…However, there has been little clinical data with regard to the effects of MK615 against cancer. One study with a small number of clinical cases showed that MK615 was useful for malignant melanoma [15] , and the clinical efficacy and safety of MK615 has been reported for patients with chronic liver disease [17] . However, the clinical benefit of MK615 for HCC patients has not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Although the activities underlying the antitumor effects have been reported to include the induction of apoptosis [5,8] , autophagy [12,16] and the suppression of aurora A kinase [9,11] , the exact mechanism(s) of action of MK615 are still being elucidated. A large amount of basic data regarding the effects of MK615 against cancer cells in vitro have been published [5][6][7][8][9][10][11][12][13][14][15][16] . However, there has been little clinical data with regard to the effects of MK615 against cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It contains several triterpenoids and has been shown to exert an anti-neoplastic effect against human cancers, such as breast cancer, stomach cancer, hepatocellular carcinoma, colon cancer and malignant melanoma. The mechanisms responsible for the anti-neoplastic effects of MK615 include induction of apoptosis and autophagy, and suppression of Aurora A kinase in cancer cells (Nakagawa et al, 2007;Adachi et al, 2007;Okada et al, 2007;Mori et al, 2007;Matsushita et al, 2010).…”
Section: Anti-cancer Effects Of An Extract From Umementioning
confidence: 99%